Drug-trip abroad : American drug-refugees in Amsterdam and London - Cuskey, Walter R.; Klein, Arnold William; Krasner, William, 1917-2003 (University of Pennsylvania Press, 1972)
This book is intended to be impressionistic. It uses solid documentation and background, but the primary intent is to show the current drug-scenes in London and Amsterdam--and, by extension, North America--through the perceptions, feelings, insights, and experiences of those who have lived them. Informed observers and specialists look and comment; the drug-takers and abusers describe their lives. The material is organized by the logic of a documentary account rather than of a socio-medical study. The soft-drug scene in Amsterdam, the lighter and shorter section comes first; the hard-drug scene and the addicts who have fled North America for London come after. Most of the more weighty material--background, documentation, conclusions--gravitates toward the end of the section or the book. This book is concerned with fact. It is also concerned with the broader truths that emerge when real human experience is presented and understood.